MENINGKATKAN KEMAMPUAN SISWA MENULIS PUISI DENGAN MENGGUNAKAN MEDIA GAMBAR [Improving Students 'Capabilities in Writing Poetry Using Images Media] - - sakila (TOTOBUANG, 2017)
The purpose of this study was  improving the process of learning to write poetry of the students of class VII C SMP Negeri 2 Singkawang in academic year 2016/2017. This research was conducted using classroom action research through 2 cycles, each cycle consists of four stages of planning, actuating, observation, and reflection. Data sources were obtained from learning activities, information from Indonesian language teachers and documents. Data collection used observation, interviews and tests. The research instrument was applied to measure the skill of writing poetry of the students which consisted of the unity of the dictionand the theme, event and the lines of poetry. The conclusion of this research showed that the use of image media in learning to write poetry of students of class VII C SMPN 2 Singkawang was able to improve students' ability in learning of writing poetry. This could be seen from the increasement of predetermined indicators. Percentage of attention and concentration of students during apperception andlearning writing poetry  had increased significantly at the time.Tujuan penelitian ini adalah untuk meningkatkan proses pembelajaran menulis puisi pada siswa kelas VII C SMP Negeri 2 Singkawang tahun ajaran 2016 / 2017. Penelitian ini menggunakan penelitian tindakan kelas yang dilaksanakan melalui 2 siklus, masing-masing siklus terdiri dari 4 tahap yaitu perencanaan, pelaksanaan, observasi dan refleksi. Sumber data diperoleh dari kegiatan pembelajaran, informasi dari gur Bahasa Indonesia dan dokumen. Pengumpulan data menggunakan observasi, wawancara dan tes. Instrumen penelitian yang digunakan bertujuan untuk mengukur keterampilan menulis puisi pada siswa terdiri dari aspek kesatuan pilihan kata dengan tema, peristiwa dan larik-larik puisi. Berdasarkan hasil penelitian diperoleh kesimpulan bahwa penggunaan media gambar dalam pembelajaran menulis puisi pada siswa kelas VII C SMPN 2 Singkawang mampu meningkatkan kemampuan siswa dalam pembelajaran menulis puisi. Hal ini dapat diketahui dari adanya peningkatan indikator-indikator yang telah ditetapkan. Persentase perhatian dan konsentrasi siswa selama apersepsi dan pada saat pembelajaran menulis puisi mengalami peningkatan yang cukup signifikan.